Biodiesel fuel production by methanolysis of fish oil derived from the discarded parts of fish catalyzed by Carica papaya lipase - P. Pinyaphong (2018)
In this paper, naturally immobilized lipase, Carica papaya lipase, catalyzed biodiesel production from fish oil was studied. The refined fish oil, extracted from the discarded parts of fish, was used as a starting material for biodiesel production. The effects of molar ratio of oil: methanol, lipase dosage, initial water activity of lipase, temperature and solvent were investigated. It was found that Carica papaya lipase was suitable for methanolysis of fish oil to produce methyl ester. The maximum yield of methyl ester could reach up to 83% with the optimal reaction conditions: oil: methanol molar ratio of 1: 4, 20% (based on oil) of lipase, initial water activity of lipase at 0.23 and 20% (based on oil) of tert-butanol at 40°C after 18 h of reaction time. There was negligible loss in lipase activity even after repeated use for 30 cycles.